Different adsorbed gas effects on the reservoir parameters and production in coalbed methane extraction by multibranch horizontal wells. Issue 4 (23rd December 2019) - Li, Qixian; Xu, Jiang; Peng, Shoujian; Yan, Fazhi; Zhang, Chaolin; Han, Ende
Abstract: Coalbed methane (CBM) is an efficient energy source that mainly contains CH4 and CO2 . Multibranch horizontal wells (MBHWs) are widely used in CBM extraction. In the study, CH4 and CO2 were employed to perform CBM extraction experiments by MBHWs. Based on the experiments, a phenomenon occurs wherein gas from the high‐pressure production layer enters the low‐pressure production layer during the initial stage. Reservoir pressure, temperature, permeability, and instantaneous flow rate exhibit similar evolution laws. Specifically, they initially increase sharply, then declining rapidly, and finally level off in the production layer with the minimum initial pressure. Increase in the adsorption capacity lowers the increase in reservoir pressure, although the phenomenon persists longer from appearance to disappearance. The moment of permeability recovery is related to the adsorption capacity, and the moment of permeability recovery under CO2 conditions occurs after that under CH4 conditions. The instantaneous flow rate curve is divided into three categories, namely steep flow rate increase curve, flow rate inhibition curve, and backflow curve. The results are useful for CBM extraction of multiple coal seams. Abstract : To study the dynamic evolution of production and reservoir parameters, large‐scale physical coalbed methane (CBM) extraction experiments were conducted.